2011
DOI: 10.1097/iae.0b013e3181eef2c7
|View full text |Cite
|
Sign up to set email alerts
|

360° Retinectomy for the Treatment of Complex Retinal Detachment

Abstract: The anatomical results of this series are comparable with those in the reported literature and indicate that vitrectomy with 360° retinectomy can be beneficial in the management of complex retinal detachments in otherwise unsalvageable eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 33 publications
(54 reference statements)
3
41
1
5
Order By: Relevance
“…Previous studies reported recurrent RD after 180°–360° retinectomies from 17 to 48 %. Our study found a higher rate of recurrent RD; however, most of the studies excluded eyes with PVR greater than C2 [9, 10]. …”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previous studies reported recurrent RD after 180°–360° retinectomies from 17 to 48 %. Our study found a higher rate of recurrent RD; however, most of the studies excluded eyes with PVR greater than C2 [9, 10]. …”
Section: Discussionmentioning
confidence: 59%
“…Postoperative hypotony is a common complication after large retinectomy and previous studies have reported a 15–40 % rate in eyes that underwent a 360° retinectomy [1013]. Additionally, Teke et al [9] reported 1.7 % phthisical eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, perfluorodecalin is used to reattach the retina and express subretinal hemorrhage, particularly if a 360-degree retinotomy has been created. [20] In such cases, the residual peripheral retina is excised completely to forestall the development of anterior proliferative vitreoretinopathy with cyclitic membrane formation and hypotony. If retina is incarcerated in the wound or if there is an extensive retinal break, silicone oil tamponade is used typically.…”
Section: Surgical Approach: Staged Surgerymentioning
confidence: 99%